2016
DOI: 10.1016/j.jphs.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of S-allyl-l-cysteine derivatives against endoplasmic reticulum stress-induced cytotoxicity is independent of calpain inhibition

Abstract: S-allyl-l-cysteine (SAC) is known to have neuroprotective properties. We synthesized various SAC derivatives and tested their effects on endoplasmic reticulum stress-induced neurotoxicity in cultured hippocampal neurons (HPNs). Among the compounds tested, S-propyl-l-cysteine (SPC) exhibited the strongest neuroprotective activity in HPNs, followed by S-ethyl-l-cysteine (SEC) and S-methyl-l-cysteine (SMC). Unlike SAC and SMC, SPC and SEC did not have inhibitory activity on μ-calpain, suggesting that the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…However, in other studies, SAC (as opposed to DATS) did not exhibit significant inhibitory effects on inflammatory mediator production in LPS-stimulated microglial cells in vitro (Ho and Su, 2014). Although SAC clearly has beneficial effects in many models of disease (ranging from diabetic complications to hypertension) (Park et al, 2014;Denzer et al, 2016;Imai et al, 2016;Uzun et al, 2016;Brahmanaidu et al, 2017;Kattaia et al, 2017), it is likely that its pharmacological effects encompass multiple additional actions beyond H 2 S donation.…”
Section: Natural H 2 S Donorsmentioning
confidence: 86%
“…However, in other studies, SAC (as opposed to DATS) did not exhibit significant inhibitory effects on inflammatory mediator production in LPS-stimulated microglial cells in vitro (Ho and Su, 2014). Although SAC clearly has beneficial effects in many models of disease (ranging from diabetic complications to hypertension) (Park et al, 2014;Denzer et al, 2016;Imai et al, 2016;Uzun et al, 2016;Brahmanaidu et al, 2017;Kattaia et al, 2017), it is likely that its pharmacological effects encompass multiple additional actions beyond H 2 S donation.…”
Section: Natural H 2 S Donorsmentioning
confidence: 86%
“…Among these are S-methyl-L-cysteine (SMC), S-ethyl-L-cysteine (SEC) and S-propyl-L-cysteine (SPC), three typical hydrophilic cysteine-containing compounds naturally found in garlic (27). More recently, we synthesized various structurally related derivatives of SAC and examined their neuroprotective effects in a model of ER stress based on tunicamycin-induced neurotoxicity in rat cultured hippocampal neurons (28) Cultured hippocampal neurons were treated with tunicamycin (10 µg/ml) in the absence or presence of 1 µM of a SAC derivative. These experiments demonstrated that the neuroprotective effects of the side-chain substituted SAC derivatives, SEC and SPC, against ER stress-induced cytotoxicity were more potent than those of SAC (Fig.…”
Section: Analogs Of Sacmentioning
confidence: 99%
“…Few synthetic derivatives of S-allyll-cysteine (SAC) also showed the same effect. Among them, S-propyl-l-cysteine (SPC) was the strongest one [33].…”
Section: Neuroprotective Effectmentioning
confidence: 99%